Implementing a Careers and Professional Development Course for Sociology Students. (January 2020) - Senter, Mary Scheuer
Sociology students are interested in having meaningful careers that use their sociological knowledge and skills, and higher education institutions are under pressure to show that their graduates achieve career success. A one-credit-hour course focused on careers, professional development, and resources for sociology majors can increase students' confidence that multiple options exist for them in their postbaccalaureate lives. Sociology faculty can design a course that increases students' ability to locate and apply for relevant jobs and graduate programs and to practice skills that employers say that want to see in college graduates. Detailed examples of assignments, readings, and class activities are presented that can readily be tailored to the unique circumstances of different institutions and their students.